Perancangan Sistem Penilaian Kinerja Perusahaan Berbasis Web Menggunakan Metode Balanced Scorecard (BSC) - Muhammad Alfarizi Harahap; Marina Elsera; Edrian Hadinata (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The balanced scorecard is a set of performance measures that cover four Kategori Produks, namely financial, customer, internal business processes and learning and growth. The word "balanced" in the balanced scorecard means that in measuring performance there must be a balance between financial measures and non-financial measures (operational measures). Data processing is carried out using the web-based Balanced Scorecard method from this data processing. used At this stage the author provides the needs of making applications related to measuring the performance of CV. Unibroom Indonesia. To design a performance measurement application based on the Balanced Scorecard method by making a mapping per unit and per year to input the Kategori Produk, Values s and key performance indicators of each unit, Input the target for each poduct from each unit for the Balanced Scorecard process. total unit value based on the total value of each Category Product. The unit score scale itself consists of a scale of 1 to 5, where the smaller the unit score value indicates that the unit's performance is considered low and the higher the unit score value indicates that the unit's performance is considered good. The company's performance appraisal system that was built can make it easier for each division within the company to determine the condition of the company's performance for each unit as a whole by looking at the four Balanced Scorecard Category Product, namely the financial, customer, internal business Kategori Produk as well as the growth and learning Category Product by looking at the total of the unit score.